Antioxidant effects of some selected flavonoids: a structure-activity relationship based study - Sarian, Murni Nazira; Ahmed, Qamar Uddin; Mat So'ad, Siti Zaiton; Alhassan, A.M; Murugesu, Suganya; Perumal, Vikneswari; Syed Mohamed, S.N.A; Latif, J (Universiti Putra Malaysia, 2017)
Objective: To investigate the antioxidant and radical scavenging activities of some selected flavonoids with respect to identify key positions responsible for antioxidant effects as well as the effect of derivatisation on the antioxidative effects.